Mindfulness-Informed Guided Imagery to Target Physical Activity: A Mixed Method Feasibility and Acceptability Pilot Study - Mitchell, Alexis D.; Martin, Laura E.; Baldwin, Austin S.; Levens, Sara M. (Frontiers in Psychology, 2021)
Physical activity offers substantial mind-body health benefits and reduced mortality, yet many individuals are chronically underactive. Physical activity interventions may benefit from integrative approaches that join components of mindfulness and neurobiological models of behavior. Mindfulness increases one’s awareness of cognitions and physical sensations to potentially facilitate self-regulation, while neurobiological models such as the dual system model of health behavior offer guidance on improving physical activity intervention targets. This 2-phase study includes an initial development process to create brief (~4 minutes) mindfulness informed guided imagery audio files that target distinct cognitive and affective processes to promote physical activity. In the second phase, participants completed a 2-week pilot intervention study to gather qualitative and quantitative data on intervention feasibility and acceptability. Participants endorsed the mindfulness informed guided imagery as easy to use, enjoyable and helpful. Over a two-week intervention period participants reported positive shifts in behavior change, physical activity enjoyment, increased mindfulness during physical activity, and increased physical activity self-efficacy and satisfaction. Interview data revealed that participants increased their frequency of physical activity and tended to experience positive affect during physical activity, engaged in future oriented thinking and were able to view physical activity in a more positive light. Findings support the feasibility and acceptability of an integrative online mindfulness informed guided imagery intervention to promote physical activity enjoyment and engagement. This study extends health behavior change intervention research and provides supporting evidence for a flexible and tailorable online mindfulness-based intervention.